Iot Based Heart Rate Detector Design - Sujono, Sujono; Fuad, Tsamrul (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Heart rate is a very vital part of the human body, if the heart rate exceeds the maximum limit it will be very dangerous for the body. So we need a heart rate recording device that can store heart rate recording data so that it makes it easier to control health. This study aims to test the heart rate recording system with a comparison of a factory-made device, namely an oximeter. Making measuring instruments consists of making hardware and making software. In making hardware, several components are used, namely pulse sensors, NodeMCU, Oled and the device for making software is the Arduino IDE. Testing of the heart rate detection device is carried out by placing a pulse sensor at the tip of the finger to measure the heart rate of respondents of different ages. The test results show that the measuring tools that have been made show that manual calculations and using tools have fairly good accuracy. The results of the data obtained from the test were 60% (3 out of 5 people) who had the same heart rate using either a device or an oximeter. The average accuracy value of the heart rate recording system when compared to an oximeter is relatively small, namely 1-2 bpm.